Alexander of Aphrodisias on the Cosmos : Arabic text with English Translation, Introduction and Commentary - Genequand (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This volume contains the Arabic translations of a lost treatise by Alexander of Aphrodisias (c. AD 200) On the Principles of the Universe with English translation, introduction and commentary. It also includes an Arabic and Syriac glossary. The introduction and commentary deal in detail with the manuscripts, the translators and the exegetical tendencies of the text, as well as with its reception in Arabic philosophy. The main theme of the work is the motion of the heavenly bodies and their influence on the physical world.